A NaY / Co3O4 composite adsorption catalytic material for reducing chemical oxygen demand in water and its preparation method
Patent Information
- Application Number
- CN202610236647.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-02-28
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2046-02-28
AI Technical Summary
[0004]金属-有机框架材料(ZIF-67)热解可转化为多孔Co3O4,但其与沸石载体的高效、牢固复合仍是一大挑战
[0021] 1. Highly efficient COD removal capacity: The material works through a synergistic mechanism of "adsorption enrichment-confined catalysis". NaY zeolite first rapidly adsorbs and enriches organic matter in the water, achieving pre-concentration of pollutants and initial reduction of COD; subsequently, the captured organic matter, in the confined environment within the zeolite channels, comes into contact with highly dispersed Co3O4 active centers and is efficiently catalytically oxidized to CO2 and H2O, thereby achieving deep and continuous removal of COD, breaking through the capacity limit of simple adsorption methods.
Smart Images

Figure CN121819911B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of water treatment technology, specifically relating to a NaY / Co3O4 composite adsorption catalytic material for reducing the chemical oxygen demand of water and its preparation method. Background Technology
[0002] Industrial wastewater, agricultural runoff, and domestic sewage contain large amounts of organic pollutants, leading to increased chemical oxygen demand (COD) in water bodies and severely disrupting the aquatic ecosystem. Traditional water treatment methods, such as physical adsorption, can temporarily accumulate pollutants but cannot completely remove them, posing risks of adsorption saturation and secondary pollution. Chemical methods, such as advanced oxidation, may be costly or produce harmful intermediate products.
[0003] Zeolite molecular sieves, especially Y-type zeolites, have been widely studied as adsorbents due to their high specific surface area and ion exchange capacity. However, their limited adsorption capacity and selectivity for some organic compounds restrict their application in advanced treatment. Combining catalytically active transition metal oxides with zeolites holds promise for achieving the adsorption and degradation of pollutants through synergistic effects. However, composite materials prepared by traditional loading methods (such as impregnation) generally suffer from poor dispersion of active components, easy solubility, low catalytic efficiency, and insufficient stability, making it difficult to achieve continuous and deep COD removal in long-term operation. In recent years, sulfate radical advanced oxidation processes, represented by permonosulfate (PMS), have attracted widespread attention due to the higher oxidation potential, longer half-life, and wider pH adaptation range of the sulfate radicals they generate. However, traditional homogeneous catalytic activation of PMS suffers from problems such as difficulty in recovering metal ions and easy secondary pollution; while existing heterogeneous catalysts (such as single metal oxides) often have bottlenecks such as insufficient exposure of active sites, low PMS utilization efficiency, and poor structural stability. Therefore, developing a composite catalytic material that can efficiently and stably activate PMS and also has pollutant enrichment function is of great significance for promoting the application of advanced oxidation technology in actual wastewater treatment.
[0004] The pyrolysis of metal-organic framework (ZIF-67) can transform it into porous Co3O4, but its efficient and robust composite with zeolite supports remains a significant challenge. Developing a method for constructing structurally stable zeolite@metal oxide composites with highly dispersed and robustly encapsulated active sites under mild conditions in a single step is of great value for the development of efficient and stable water treatment technologies. Summary of the Invention
[0005] To address the shortcomings of existing technologies in simultaneously achieving efficient adsorption, deep catalysis, and long-term stability, this invention provides a NaY / Co3O4 composite adsorption catalytic material for reducing the chemical oxygen demand (COD) of water and its preparation method. This invention employs a "SiO2@ZIF-67 precursor-steam-assisted conversion" strategy, using SiO2@ZIF-67 as a precursor to achieve in-situ crystallization of NaY zeolite in a low-alkalinity steam environment. Further, through calcination, ZIF-67 undergoes thermal conversion to Co3O4. The resulting Co3O4 active centers, in the form of highly dispersed nanoparticles or clusters, are in-situ embedded and firmly anchored within the internal pores or framework of NaY zeolite. This material not only exhibits strong adsorption and enrichment capabilities for organic pollutants but also efficiently generates sulfate and hydroxyl radicals through Co3O4 catalytic activation of permonosulfate (PMS), deeply oxidizing the enriched organic pollutants. This results in efficient and stable reduction of COD in water over a wide pH range. To achieve the above objectives, this invention adopts the following technical solution:
[0006] A method for preparing a NaY / Co3O4 composite adsorption catalytic material for reducing the chemical oxygen demand (COD) of water, characterized by comprising the following steps:
[0007] S1. Preparation of SiO2@ZIF-67 precursor:
[0008] Fumed silica (SiO2) was uniformly dispersed in methanol to form suspension A. Methanol solutions of cobalt salt (solution B) and 2-methylimidazole (solution C) were prepared separately. Suspension A and solution C were mixed under vigorous stirring, and then quickly poured into solution B. The reaction was carried out at room temperature, allowing ZIF-67 to grow in situ on the surface of SiO2 particles. After the reaction was complete, the product was washed with methanol and dried to obtain a purple powdery SiO2@ZIF-67 precursor.
[0009] S2. Steam-assisted conversion:
[0010] S2.1 Preparation of the synthesis mother liquor:
[0011] Based on the mass of SiO2 in SiO2@ZIF-67 obtained in step S1, the molar ratios are n(SiO2): n(Na2O): n(Al2O3): n(H2O) = 3: (0.7~1.5): (0.04~0.08): (40~60).
[0012] Calculate and weigh sodium hydroxide (NaOH), sodium aluminate (NaAlO2), and deionized water, and mix and stir until a clear and transparent alkaline sodium aluminate solution is formed.
[0013] S2.2 Preparation of dry gel:
[0014] The SiO2@ZIF-67 precursor powder was added to the above mother liquor, stirred thoroughly, and aged at room temperature for 6-12 hours. It was then dried at 60-90°C and ground to obtain a uniform dry gel powder.
[0015] S2.3 Steam-assisted crystallization:
[0016] Add an appropriate amount of deionized water to the bottom of a reaction vessel lined with polytetrafluoroethylene (PTFE) as a steam source. Place the dry gel powder in an open container, ensuring it does not come into contact with the liquid water. Seal the reaction vessel and crystallize at 80–100°C for 24–72 hours.
[0017] S3. Calcination Transformation:
[0018] After crystallization, the product is cooled, washed, and dried to obtain an intermediate product. This intermediate product is placed in an oxygen atmosphere and heated to 350-500℃ at a rate of 0.5-2℃ / min, and then calcined at this temperature for 2-4 hours to obtain the final NaY@Co3O4 composite adsorption-catalyst.
[0019] This material possesses a stable main structure composed of well-crystallized NaY zeolite, in which the Co3O4 active centers formed by the thermal conversion of ZIF-67 are embedded in situ and firmly anchored within the internal channels or framework of NaY zeolite in the form of highly dispersed nanoparticles or clusters. This structure effectively confines and protects the Co3O4 active sites, resulting in high dispersibility, strong bonding with the zeolite carrier, and resistance to dissolution.
[0020] The beneficial effects of this invention are as follows:
[0021] 1. Highly efficient COD removal capacity: The material works through a synergistic mechanism of "adsorption enrichment-confined catalysis". NaY zeolite first rapidly adsorbs and enriches organic matter in the water, achieving pre-concentration of pollutants and initial reduction of COD; subsequently, the captured organic matter, in the confined environment within the zeolite channels, comes into contact with highly dispersed Co3O4 active centers and is efficiently catalytically oxidized to CO2 and H2O, thereby achieving deep and continuous removal of COD, breaking through the capacity limit of simple adsorption methods.
[0022] 2. Excellent catalytic oxidation and anti-interference performance: The unique confined structure concentrates the catalytic reaction within the zeolite channels, which is beneficial for the further oxidation of reaction intermediates, promotes the complete oxidation of pollutants, and reduces the generation and release of harmful byproducts. At the same time, the NaY zeolite framework has a certain sieving and shape-selective effect on inorganic ions and macromolecular organic matter, improving the selectivity and anti-interference ability of the catalytic system in actual complex water bodies.
[0023] 3. Excellent structure and operational stability: The Co3O4 active centers are confined and firmly anchored inside the zeolite channels, avoiding direct and intense contact with the reaction solution. This greatly inhibits the dissolution, loss, and agglomeration deactivation of active components, ensuring the stability of COD removal performance of the material during long-term or multiple cycles of use, and fundamentally eliminating the risk of secondary pollution caused by the dissolution of metal ions.
[0024] 4. Mild and environmentally friendly preparation process: The steam-assisted conversion method employed has low alkalinity and a mild temperature, effectively achieving a clever coupling between zeolite crystallization and in-situ formation of active centers. This process has low energy consumption, is simple to operate, has good reproducibility, and has the potential for large-scale production. Attached Figure Description
[0025] Figure 1 The XRD diffraction pattern of the sample prepared in Example 1. Detailed Implementation
[0026] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to specific embodiments. The following embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. Unless otherwise specified, all reagents and instruments used are commercially available.
[0027] Example 1:
[0028] (1) Preparation of SiO2@ZIF-67 precursor: 1.0 g of gaseous SiO2 was ultrasonically dispersed in 100 mL of anhydrous methanol. 2.91 g of Co(NO3)2·6H2O was dissolved in 200 mL of methanol (solution B), and 6.49 g of 2-methylimidazole was dissolved in 200 mL of methanol (solution C). The SiO2 suspension was poured into solution C, stirred for 10 minutes, and then quickly added to solution B. The mixture was stirred at room temperature for 6 hours. The product was washed by centrifugation with methanol and dried under vacuum at 60 °C for 12 hours to obtain SiO2@ZIF-67 powder.
[0029] (2) Preparation of mother liquor and preparation of dry gel: Take 1.5 g of SiO2@ZIF-67 powder (SiO2 is calculated as 1.0 g). Calculate the molar ratio of 3SiO2 : 1 Na2O : 0.08 Al2O3 : 40 H2O, weigh 0.399 g of NaOH, 0.289 g of NaAlO2, and 13.5 g of deionized water to prepare a clear mother liquor. Add the precursor to the mother liquor, stir and age at room temperature for 12 hours, dry at 50℃, and grind to obtain a dry gel.
[0030] Steam-assisted crystallization: Place the dry gel into an open vial, place the vial in the liner of a 50 mL reactor (with 5 mL of water at the bottom) to prevent external water from entering the vial, age at room temperature for 2 days, and then crystallize at 80°C for 48 hours.
[0031] (3) Post-treatment: After washing and drying, the product was ion-exchanged three times with 1 mol / L NH4Cl solution, and then dried again. Finally, it was calcined in oxygen at 350℃ for 4 hours at a rate of 1℃ / min. Product labeling: NaY@Co3O4-1
[0032] like Figure 1 As shown, the XRD pattern of the NaY@Co3O4-1 sample obtained by pyrolysis in an oxygen atmosphere clearly shows that the characteristic diffraction peaks of NaY zeolite are completely preserved, indicating that the zeolite crystal structure remains stable during heat treatment. However, no obvious characteristic peaks of the Co3O4 crystalline phase appear in the spectrum. This is not due to the absence of active components, but rather the result of the synergistic effect of the "SiO2@ZIF-67 precursor-steam-assisted conversion" strategy of this invention and the oxygen atmosphere: ZIF-67 in the precursor is transformed into extremely small Co3O4 nanoclusters, which are highly dispersed inside the shell or pores of NaY zeolite. Such sub-nanoscale or near-amorphous active species do not exhibit obvious crystal diffraction signals because their size is below the long-range order detection limit of XRD. This structure not only maximizes the exposure of catalytic active sites, but also enhances the interaction between the active components and the support through the confinement effect of the zeolite framework, which is beneficial to improving the catalytic efficiency and stability of the material.
[0033] Example 2:
[0034] (1) Preparation of SiO2@ZIF-67 precursor: 1.0 g of gaseous SiO2 was ultrasonically dispersed in 100 mL of anhydrous methanol. 2.91 g of Co(NO3)2·6H2O was dissolved in 200 mL of methanol (solution B), and 6.49 g of 2-methylimidazole was dissolved in 200 mL of methanol (solution C). The SiO2 suspension was poured into solution C, stirred for 10 minutes, and then quickly added to solution B. The mixture was stirred at room temperature for 6 hours. The product was washed by centrifugation with methanol and dried under vacuum at 60 °C for 12 hours to obtain SiO2@ZIF-67 powder.
[0035] (2) Preparation of mother liquor and preparation of dry gel: Take 1.5 g of SiO2@ZIF-67 powder (SiO2 is calculated as 1.0 g). Calculate the molar ratio of SiO2 : 0.7 Na2O : 0.08 Al2O3 : 40 H2O, weigh 0.279 g of NaOH, 0.289 g of NaAlO2, and 13.5 g of deionized water to prepare a clear mother liquor. Add the precursor to the mother liquor, stir and age at room temperature for 12 hours, dry at 50℃, and grind to obtain a dry gel.
[0036] Steam-assisted crystallization: Place the dry gel into an open vial, place the vial in the liner of a 50 mL reactor (with 5 mL of water at the bottom) to prevent external water from entering the vial, age at room temperature for 2 days, and then crystallize at 80°C for 72 hours.
[0037] (3) Post-treatment: After washing and drying, the product was ion-exchanged three times with 1 mol / L NH4Cl solution and then dried again. Finally, it was calcined in oxygen at 350℃ for 4 hours at a rate of 1℃ / min.
[0038] Product label: NaY@Co3O4-2
[0039] Example 3:
[0040] (1) Preparation of SiO2@ZIF-67 precursor:
[0041] 1.0 g of fumed SiO2 was ultrasonically dispersed in 100 mL of anhydrous methanol. 2.91 g of Co(NO3)2·6H2O was dissolved in 200 mL of methanol (solution B), and 6.49 g of 2-methylimidazole was dissolved in 200 mL of methanol (solution C). The SiO2 suspension was poured into solution C and stirred for 10 minutes. Then, it was rapidly added to solution B, and the reaction was carried out at room temperature with stirring for 6 hours. The product was washed by centrifugation with methanol and dried under vacuum at 60 °C for 12 hours to obtain SiO2@ZIF-67 powder.
[0042] (2) Preparation of mother liquor and preparation of dry gel:
[0043] Take 1.5 g of SiO2@ZIF-67 powder (SiO2 is calculated as 1.0 g). Based on a molar ratio of 3 SiO2 : 1 Na2O : 0.04 Al2O3 : 40 H2O, weigh out 0.399 g of NaOH, 0.145 g of NaAlO2, and 13.5 g of deionized water to prepare a clear mother liquor. Add the precursor powder to the mother liquor, stir and age at room temperature for 12 hours, dry at 50℃, and grind to obtain a dry gel.
[0044] Steam-assisted crystallization: Place the dry gel into an open vial, place the vial in the liner of a 50 mL reactor (with 5 mL of water at the bottom) to prevent external water from entering the vial, age at room temperature for 2 days, and then crystallize at 80°C for 60 hours.
[0045] (3) Post-treatment: The product was washed and dried with deionized water, then subjected to three ion exchanges with 1 mol / L NH4Cl solution, and dried again. Finally, it was calcined at 350℃ for 4 hours in an oxygen atmosphere at a heating rate of 1℃ / min. Product label: NaY@Co3O4-3
[0046] Example 4:
[0047] (1) Preparation of SiO2@ZIF-67 precursor: 1.0 g of gaseous SiO2 was ultrasonically dispersed in 100 mL of anhydrous methanol. 2.91 g of Co(NO3)2·6H2O was dissolved in 200 mL of methanol (solution B), and 6.49 g of 2-methylimidazole was dissolved in 200 mL of methanol (solution C). The SiO2 suspension was poured into solution C, stirred for 10 minutes, and then quickly added to solution B. The mixture was stirred at room temperature for 6 hours. The product was washed by centrifugation with methanol and dried under vacuum at 60 °C for 12 hours to obtain SiO2@ZIF-67 powder.
[0048] (2) Preparation of mother liquor and preparation of dry gel: Take 1.5 g of SiO2@ZIF-67 powder (SiO2 is calculated as 1.0 g). Calculate the molar ratio of 3SiO2 : 1 Na2O : 0.08 Al2O3 : 60 H2O, weigh 0.399 g of NaOH, 0.289 g of NaAlO2, and 20.25 g of deionized water to prepare a clear mother liquor. Add the precursor to the mother liquor, stir and age at room temperature for 12 hours, dry at 50℃, and grind to obtain a dry gel.
[0049] Steam-assisted crystallization: Place the dry gel into an open vial, place the vial in the liner of a 50 mL reactor (with 5 mL of water at the bottom) to prevent external water from entering the vial, age at room temperature for 2 days, and then crystallize at 80°C for 48 hours.
[0050] (3) Post-treatment: After washing and drying, the product was ion-exchanged three times with 1 mol / L NH4Cl solution and then dried again. Finally, it was calcined in oxygen at 350℃ for 4 hours at a rate of 1℃ / min.
[0051] Product label: NaY@Co3O4-4
[0052] Example 5:
[0053] (1) Preparation of SiO2@ZIF-67 precursor: 1.0 g of gaseous SiO2 was ultrasonically dispersed in 100 mL of anhydrous methanol. 2.91 g of Co(NO3)2·6H2O was dissolved in 200 mL of methanol (solution B), and 6.49 g of 2-methylimidazole was dissolved in 200 mL of methanol (solution C). The SiO2 suspension was poured into solution C, stirred for 10 minutes, and then quickly added to solution B. The mixture was stirred at room temperature for 6 hours. The product was washed by centrifugation with methanol and dried under vacuum at 60 °C for 12 hours to obtain SiO2@ZIF-67 powder.
[0054] (2) Preparation of mother liquor and preparation of dry gel: Take 1.5 g of SiO2@ZIF-67 powder (SiO2 is calculated as 1.0 g). Calculate the molar ratio of 3SiO2 : 1.5Na2O : 0.08Al2O3 : 40H2O, weigh 0.599 g of NaOH, 0.289 g of NaAlO2, and 13.5 g of deionized water to prepare a clear mother liquor. Add the precursor to the mother liquor, stir and age at room temperature for 12 hours, dry at 50℃, and grind to obtain a dry gel.
[0055] Steam-assisted crystallization: Place the dry gel into an open vial, place the vial in the liner of a 50 mL reactor (with 5 mL of water at the bottom) to prevent external water from entering the vial, age at room temperature for 2 days, and then crystallize at 80°C for 48 hours.
[0056] (3) Post-treatment: After washing and drying, the product was ion-exchanged three times with 1 mol / L NH4Cl solution and then dried again. Finally, it was calcined in oxygen at 350℃ for 4 hours at a rate of 1℃ / min.
[0057] Product label: NaY@Co3O4-5
[0058] Comparative Example 1:
[0059] Impregnation-roasting method (20% loading)
[0060] 2.0 g of commercial NaY molecular sieve (SiO2 / Al2O3≈5.1) was weighed and dispersed in 100 mL of water. Based on a Co3O4 loading of 20 wt.%, 1.746 g of Co(NO3)2·6H2O was weighed and added to the suspension. The mixture was magnetically stirred at room temperature for 12 hours. The mixture was then evaporated to dryness in an 80°C water bath, followed by drying overnight in a 100°C oven and grinding. The resulting powder was calcined in an oxygen atmosphere at a temperature increased to 500°C at a rate of 5°C / min for 4 hours. Product label: Co3O4 / Y-IMP
[0061] Comparative Example 2:
[0062] Pure NaY molecular sieve
[0063] (1) Preparation of mother liquor: Based on the molar ratio of 3 SiO2 : 1 Na2O : 0.08 Al2O3 : 40 H2O, weigh 1.0 g of gaseous SiO2 as the silicon source, and weigh 0.399 g of NaOH, 0.289 g of NaAlO2 and 13.5 g of deionized water accordingly.
[0064] (2) Synthesis and Post-treatment: SiO2 was added to a prepared alkaline sodium aluminate solution, stirred and aged at room temperature for 12 hours, and then dried and ground at 80°C to obtain a dry gel. Crystallization was carried out under the same steam-assisted crystallization conditions as in Example 1 (80°C, 48 hours). After washing and drying, the product was ion-exchanged three times with 1 mol / L NH4Cl solution, and then dried again. Finally, it was calcined in oxygen at 350°C for 4 hours at a rate of 1°C / min. Product label: NaY-Pure
[0065] Performance testing:
[0066] COD removal experimental testing method: Actual landfill leachate was used as the test object, with an initial COD concentration of approximately 1100-1200 mg / L. The catalytic oxidation performance of the material of this invention under low-concentration PMS conditions was investigated.
[0067] Specific steps: Take 200 mL of landfill leachate into a 250 mL Erlenmeyer flask and adjust the initial pH to the appropriate value (3.0 or 5.0). Add 100 mg of the catalyst sample to be tested (corresponding to a concentration of 0.5 g / L). Simultaneously add a certain amount of permonosulfate (PMS) to make the initial PMS concentration in the system 0.3 mmol / L or 0.5 mmol / L. Place the reaction system on a thermostatic magnetic stirrer, controlling the reaction temperature at 30℃ and the stirring speed at a constant speed. Take samples at specific time points, immediately centrifuge to separate the supernatant, and determine the COD value of the filtrate using the standard potassium dichromate method to calculate the COD removal rate.
[0068] Cyclic stability testing was conducted: After one reaction was completed, the catalyst was recovered, washed, dried, and used in the next round of landfill leachate treatment experiments to examine the retention of COD removal rate after multiple cycles.
[0069] Table 1 Performance Tests of Examples 1-2 and Comparative Examples 1-2
[0070] <![CDATA[NaY@Co3O4-2]]> 3.0 30 1150 1.0 0.5 96.2 <![CDATA[NaY@Co3O4-1]]> 3.0 30 1150 1.0 0.5 91.5 <![CDATA[Co3O4 / Y-IMP]]> 3.0 30 1150 1.0 0.5 68.4 NaY-Pure 3.0 30 1150 1.0 0.5 38.7
[0071] Conclusion: The NaY@Co3O4 composite material prepared in this invention significantly outperforms traditional materials in COD removal from actual landfill leachate. Among them, the NaY@Co3O4-2 sample prepared under optimized conditions showed the best performance, with a COD removal rate of 96.2%; the NaY@Co3O4-1 sample also maintained an excellent level with a removal rate of 91.5%. In contrast, the Co3O4 / Y-IMP material prepared by the traditional impregnation-calcination method only achieved a COD removal rate of 68.4% under the same conditions; pure NaY zeolite (NaY-Pure) had the lowest removal rate, at only 38.7%. The results indicate that the preparation method proposed in this invention can effectively improve the adsorption-catalytic synergistic performance of the composite material, giving it superior COD removal capacity in the treatment of high-concentration organic wastewater.
[0072] Table 2: Cyclic stability test (NaY@Co3O4-2 vs. Co3O4 / Y-IMP)
[0073] 1st time 88.5 68.4 2nd time 87.2 55.1 3rd 86.0 42.3 4th 84.8 31.5 5th 83.5 22.8 Dissolution testing Co ion dissolution < 0.1 mg / L After the third treatment, Co ion dissolution was > 2.5 mg / L
[0074] Conclusion: All NaY@Co3O4 materials prepared using the method of this invention exhibited excellent COD removal performance for actual landfill leachate. Especially noteworthy is their ability to efficiently activate PMS under near-neutral and even weakly alkaline conditions, achieving deep oxidation of pollutants. This is achieved not only through efficient pollutant enrichment via zeolite but, more importantly, by dispersing the catalytically active centers (Co3O4) within the NaY zeolite shell or pores. This allows for efficient and stable activation of PMS in a confined environment, continuously generating highly oxidizing sulfate and hydroxyl radicals, thereby achieving deep degradation of pollutants and effectively preventing the dissolution of metal ions. Example 2 demonstrated the best performance, showcasing a powerful and stable treatment capability for complex actual wastewater. This invention overcomes the limitations of traditional adsorbent materials (limited capacity), traditional supported catalysts (poor stability), and homogeneous / heterogeneous PMS activation technologies (strong pH dependence, easy metal dissolution, and low PMS utilization efficiency). It provides a highly efficient, stable, and environmentally friendly novel solution for the deep treatment of challenging organic wastewater.
[0075] The above description is merely a specific embodiment of the present invention, enabling those skilled in the art to understand or implement the invention. Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the invention. Therefore, the present invention is not to be limited to the embodiments described herein, but is to be accorded the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A method for preparing a NaY / Co3O4 composite adsorption catalytic material for reducing the chemical oxygen demand (COD) of water, characterized in that, Includes the following steps: (1) Preparation of SiO2@ZIF-67 precursor: Disperse gaseous SiO2 in the first solvent to obtain a suspension; Cobalt salt and 2-methylimidazole were dissolved in a second solvent to obtain solution B and solution C, respectively. The suspension was first mixed with solution C, and then the resulting mixture was mixed with solution B to carry out the reaction. After the reaction was completed, the mixture was washed and dried to obtain SiO2@ZIF-67 powder. (2) Steam-assisted crystallization synthesis of NaY zeolite: The SiO2@ZIF-67 powder obtained in step (1) is used as silicon source and cobalt source, mixed with sodium source, aluminum source and water to prepare a mother liquor, and after aging and drying, a dry gel is obtained; the dry gel is placed in an open bottle, and the open bottle is placed in the liner of a reaction vessel with an appropriate amount of deionized water as a steam source, and external water is prevented from entering the bottle. The dry gel is aged and crystallized in a steam atmosphere to obtain an intermediate coated with NaY zeolite; (3) Post-processing: The product obtained in step (2) is subjected to ion exchange and drying in sequence, and then calcined in an oxygen-containing atmosphere to obtain the NaY@Co3O4 composite material, wherein the composite material uses NaY zeolite as a carrier and Co3O4 as an active component; the Co3O4 is embedded in situ and firmly anchored in the internal pores or skeleton of NaY zeolite.
2. The preparation method of the NaY / Co3O4 composite adsorption catalytic material for reducing the chemical oxygen demand of water according to claim 1, characterized in that, In step (1), the molar ratio of gaseous SiO2 to cobalt in the cobalt salt is 1:(0.5-5), and the molar ratio of cobalt in the cobalt salt to 2-methylimidazole is 1:(2-10); the reaction conditions are: stirring at 15-35℃ for 4-12 hours.
3. The preparation method of the NaY / Co3O4 composite adsorption catalytic material for reducing the chemical oxygen demand of water according to claim 1, characterized in that, In step (2), the molar ratio of each material in the mother liquor is: SiO2 : Na2O : Al2O3 : H2O = 3 : (0.7~1.5): (0.04~0.08) : (40~60); wherein, SiO2 is based on the mass of the gaseous SiO2 used in step (1).
4. The preparation method of the NaY / Co3O4 composite adsorption catalytic material for reducing the chemical oxygen demand of water according to claim 1, characterized in that, In step (2), the conditions for the crystallization reaction are: first, age at 15-35℃ for 1-3 days, and then crystallize at 70-100℃ for 24-96 hours.
5. The preparation method of the NaY / Co3O4 composite adsorption catalytic material for reducing the chemical oxygen demand of water according to claim 1, characterized in that, In step (3), the ion exchanger used is an ammonium salt solution; the calcination conditions are: heating to 350-500℃ at a rate of 0.5-2℃ / min and holding at that temperature for 2-6 hours.
6. The preparation method of the NaY / Co3O4 composite adsorption catalytic material for reducing the chemical oxygen demand of water according to claim 5, characterized in that, The calcination is carried out in an oxygen atmosphere, with a heating rate of 1℃ / min, a calcination temperature of 350℃, and a calcination time of 4 hours.
7. A NaY / Co3O4 composite adsorption catalytic material for reducing the chemical oxygen demand (COD) of water, characterized in that, Prepared by the method according to any one of claims 1 to 6.
8. The application of the NaY@Co3O4 composite material as described in claim 7 in the catalytic degradation of organic pollutants, characterized in that, The composite material is used to activate persulfate to degrade organic pollutants in wastewater.
Citation Information
Patent Citations
Zeolite-based cobalt catalyst and preparation method and application thereof
CN121513945A